2008
DOI: 10.1097/cad.0b013e3282f21376
|View full text |Cite
|
Sign up to set email alerts
|

High-dose methotrexate in adults with osteosarcoma: a population pharmacokinetics study and validation of a new limited sampling strategy

Abstract: Preoperative high-dose methotrexate (HD-MTX) with folinic acid (leucovorin) rescue is still a mainstay in the treatment of osteosarcoma. This anticancer agent is characterized by a narrow therapeutic index and wide interpatients variability. To ensure effective and safe administration of HD-MTX, we had earlier developed an adaptive-dosing schedule with a feedback strategy. In our institute, the MTX dosage was tailored according to individual pharmacokinetics parameters, determined in real time both from two bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 28 publications
7
37
0
Order By: Relevance
“…Similar to prior adult studies, we showed that among our pediatric cohort BSA and BMI were inconsistently associated with adverse treatment outcomes. Patients with lower BSA were more likely to have chemotherapy holds and neutropenia, while patients with higher BMI experienced more thrombocytopenia …”
Section: Discussionmentioning
confidence: 99%
“…Similar to prior adult studies, we showed that among our pediatric cohort BSA and BMI were inconsistently associated with adverse treatment outcomes. Patients with lower BSA were more likely to have chemotherapy holds and neutropenia, while patients with higher BMI experienced more thrombocytopenia …”
Section: Discussionmentioning
confidence: 99%
“…The IC 50 values were determined by interpolation from dose-response curves. A total of 100 lM was chosen as maximal concentration because much higher doses do not normally reach the blood plasma, 19 and we are looking for compounds with high activity (low IC 50 ) which could eventually be used in the future as a drug for chemotherapy with very low to no side effects.…”
Section: Inhibition Of Tumor Cell Proliferationmentioning
confidence: 99%
“…, 4-bromo(17), and 4-nitro (18) or an electron donating group like 4-methoxyl (13) and 4-methyl(19) exhibited moderate activities with IC 50 values of 25.7, 22.5, 43.0, 46.4 and 41.5 lM, respectively. Furthermore, compound 7 bearing 3-methoxy-4-hydroxy group and 9 bearing 2,5-dihydroxy group exhibited negligible anti-proliferation response in both the cell lines Hep G2 and Colon 205.…”
mentioning
confidence: 98%
“…Table 2 summarizes LSSs for various anticancer agents and their level of evidence. There were 8 citations for bulsufan (one level II-1, 6 level II-2, one level III) [12][13][14][15][16][17][18][19], one citation for cladribine (level II-1) [20], one citation for cyclophosphamide (level II-1) [21], two citations for docetaxel (one level II-1, one level III) [22,23], one citation for doxorubicin (level II-1) [24], 3 citations for epirubicin (one level II-1, 2 level III) [25][26][27], 7 citations for etoposide (3 level I, 2 level II-1, one level II-2, one level III) [3,[28][29][30][31][32][33][34], 4 citations for 5-fluorouracil (one level II-1, one level II-2, 2 level III) [35][36][37][38], 6 citations for irinotecan (2 level I, 3 level II-2, one level III) [39][40][41][42][43][44], one citation for melphalan (level I) [45], 4 citations for methotrrexate (2 level II-1, one level II-2) [46][47][48][49], one citation for temozolamide (level I) [10], one citation for thiotepa (level III) [50], 6 citations for topotecan (3 level I, one l...…”
Section: Resultsmentioning
confidence: 99%